Summary Guidance for Daily Practices on Glycemic Control and Foot Care Behavior - Devi Mediarti; Rosnani Rosnani; Hidayat Arifin (Universitas Airlangga, 2020)
Introduction: The Prevalence of Diabetes Foot Ulcers (DFU) in Indonesia is increasing every year. Summary Guidance for Daily Practice (SGFDP) is a media used to discuss and share knowledge to prevent foot ulcer in patients with Type 2 Diabetes Mellitus (T2DM). The aim was to know the influence of applying SGFDP on glycemic control (fasting blood glucose levels) and foot care behavior.Methods: The study was quasi-experimental utilizing a pretest-post-test with a control group design. The sample obtained was 232 respondents through consecutive sampling. The variables were SGFDP, glycemic control, and foot care behavior. The intervention was conducted for three weeks meeting. The data collected using observation sheets and the Nottingham Assessment of Functional Footcare (NAFF) questionnaire. The results were analyzed using the Wilcoxon and Mann-Whitney tests.Results: Most of respondents were elderly aged 41-50 years old. Respondents showed significant progressed of foot care behavior on before and after treatment. The results showed a significant influence from SGFDP on foot care behavior (p=0.001).Conclusion: The application of SGFDP as an approach to prevent foot ulcers among adults T2DM was significantly affected. It was conducted by discussing and sharing knowledge and utilizing a foot ulcer prevention simulation with foot exercises. Sharing information and the attention given by the nurses in the form of regular meetings can increase patient knowledge and induce behavior changes among adult T2DM.